Explore 360 [degrees] Pompeii - Chrisp, Peter; Vongprachanh, Somchith (London Carlton Books Limited, 2015)
Nearly two thousand years ago, the ancient Roman city of Pompeii was buried in ash from a massive volcanic eruption and frizen in time. Transport yourself back and relive one of the most dramatic moments in history. Sumptuous large-scale photos and realistic artworks recreate the city when people still lived there, while a CD-ROM with 3D-modelled animations lets you navigate the town room by room. Stroll through the forum - Pompeii's impressive town square, take a tour of the busy public baths, visit a Roman bakery and peek inside a wealthy merchant town house.
Degree symbol used in title.
"Step inside the remarkable Roman city on a 3D interactive tour"--Cover.
Includes some fold-out pages.
Keywords: Pompeii (Extinct city) -- Juvenile literature; Vesuvius (Italy) -- Eruption, 79 -- Juvenile literature